Ophthalmological aspects of sportive activities = (NoFTALXMOLOG)QÆ^NÆ ASPEKTI SPORTIWNOÇ DÆQLXNOSTÆ (B/s)E - Dr., med. Jan Verbeck (2018)
The article deals with the ophthalmological issues of sports. Risky aspects and possibilities to prevent harms to the eyes of an athlete are analysed. It has been shown that reduced visual acuity can also be a reason for very serious injuries caused by sportive activity
(Nu STATT)QÆ WISWÆTLENO OFTALXMOLOGÆ^NÆ PROBLEMI SPORTU(B. (NpROANALÆZOWANO POTENCÆJNÆ RIZIKI(B, (NPREDSTAWLENO ZASOBI DLQ PROFÆLAKTIKI POGÆR[ENNQ ZORU W SPORTSMENÆW(B. (NdOWEDENO(B, (N]O ZNIVENNQ GOSTROTI ZORU MOVE BUTI NASLÆDKOM SPORTIWNIH TRAWMs)E
(Nb)QÆBLÆOGR(B. (NW KÆNCÆ ST(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NOFTALXMOLOG)QÆQs)E; (NSPORTs; (NTRAWMAs; ophthalmology; sport; injury